THE MORPHOLOGICAL CHANGES OF THE WHITE RATS’ THYROID GLAND 21 DAYS AFTER EXPERIMENTAL THERMAL BURN INJURY UNDER NaCl SYSTEMIC ADMINISTRATION - Tiron, O.I.; Stetsenko, A.V.; Yatsyna, O.I.; Zayats, L.M.; Kolotvin, A.O.; Shumilina, K.S. (World of Medicine and Biology, 2022)
The histological features of the experimental animals’ thyroid gland 21 days after modelled burn injury under NaCl systemic administration can be described as adaptive and compensatory processes in the follicular wall, vascular and stromal components. Most of the thyroid follicles were round or oval in shape, some of them were overstretched and filled with dense colloid. The follicular epithelial cells were flattened, contained pyknotic nuclei surrounded by thin layer of cytoplasm. In some regions it was observed the desquamation of the thyrocytes within the follicular lumen. The electron microscopic examination of the gland 21 days after modelled burn confirmed the changes that had been previously established by the analysis of histological specimens. The flattened thyrocytes contained osmiophilic nuclei with heterochromatin. Their cytoplasm was electron lucent and contained organelles exhibiting the signs of destruction. The microvilli were observed on the apical domain of thyrocytes. Along with the follicles with altered histological structure (which indicates an imbalance in the synthesis and excretion of hormones) there were observed the follicles with intact wall and unaffected blood supply. The ultrastructure of the latter indicates active protein-synthetizing and protein-secreting processes.